Mapping neurotransmitter networks with PET: An example on serotonin and opioid systems - Tuominen, Lauri; Nummenmaa, Lauri; Keltikangas-Järvinen, Liisa; Raitakari, Olli; Hietala, Jarmo (Human brain mapping, 2014)
All functions of the human brain are consequences of altered activity of specific neural pathways and neurotransmitter systems. Although the knowledge of “system level” connectivity in the brain is increasing rapidly, we lack “molecular level” information on brain networks and connectivity patterns. We introduce novel voxel‐based positron emission tomography (PET) methods for studying internal neurotransmitter network structure and intercorrelations of different neurotransmitter systems in the human brain. We chose serotonin transporter and μ‐opioid receptor for this analysis because of their functional interaction at the cellular level and similar regional distribution in the brain. Twenty‐one healthy subjects underwent two consecutive PET scans using [11C]MADAM, a serotonin transporter tracer, and [11C]carfentanil, a μ‐opioid receptor tracer. First, voxel‐by‐voxel “intracorrelations” (hub and seed analyses) were used to study the internal structure of opioid and serotonin systems. Second, voxel‐level opioid–serotonin intercorrelations (between neurotransmitters) were computed. Regional μ‐opioid receptor binding potentials were uniformly correlated throughout the brain. However, our analyses revealed nonuniformity in the serotonin transporter intracorrelations and identified a highly connected local network (midbrain–striatum–thalamus–amygdala). Regionally specific intercorrelations between the opioid and serotonin tracers were found in anteromedial thalamus, amygdala, anterior cingulate cortex, dorsolateral prefrontal cortex, and left parietal cortex, i.e., in areas relevant for several neuropsychiatric disorders, especially affective disorders. This methodology enables in vivo mapping of connectivity patterns within and between neurotransmitter systems. Quantification of functional neurotransmitter balances may be a useful approach in etiological studies of neuropsychiatric disorders and also in drug development as a biomarker‐based rationale for targeted modulation of neurotransmitter networks. Hum Brain Mapp 35:1875–1884, 2014. © 2013 Wiley Periodicals, Inc.